Social Capital Profile of Beef Cattle Farmer in Transmigration Area in Tebo Regency, Jambi Province , Indonesia - Hadi, Syafril (2014)
Acceptation or modification in innovation by cattle farmercould be approached by social capital since the elements in social capital include communication networks, trust, and norms between individuals, which could enhance awareness and assuredness to improve productivity of beef production. An important study has been carried out to analyze the significant of social capital influence on productivity improve ment of beef production in transmigration area of Rimbo Bujang and Rimbo Ulu, Tebo Regency, Jambi Province of Indonesia. Three major elements of social capital that being observed in this study include (1) trusts; (2) norms or policies; and (3)corporation networks, which include individual and collective corporation networks. Results show that social capital level of cattle farmer is in high category, correspondingly to social capital forming elements, such as trust, norms,and corporation network. Strong bind of this social capital can be an asset for the community to be more productive, improvement on corporation network, social relationship and interaction among farmers or community for innovation information access, corporation in farming activity and innovation practice to improve beef production.